Ultrasound-Assisted Extraction of Natural Pigments From Food Processing By-Products: A Review - Linares, Guillermo; Rojas, Meliza Lindsay (Frontiers in Nutrition, 2022)
Ultrasound is an emerging technology, which has been highly explored in the food area to improve processes and products. When ultrasound is applied to a product with solid or fluid characteristics, the passage of acoustic waves and acoustic cavitation generates different mechanisms responsible for modifications in the original matrix of the sample. These effects of ultrasound can also be used to take advantage of by-products, for example by extracting compounds of interest, including natural pigments. Natural pigments or colourants are being highly demanded by different industries not only for colour purposes but also due to their healthy properties, the greater demands in regulations and new consumer preferences. This review presents an updated critical analysis of the application of ultrasound-assisted extraction (UAE) to obtain natural pigments from food processing by-products. Initially, the ultrasound effects and mechanisms that improve the extraction of natural pigments in a fluid medium, as well as the factors that influence the extraction and the energy consumption of UAE are analysed and described. Subsequently, the UAE application to obtain pigments belonging to the groups of carotenoids, chlorophyll, anthocyanins and betalains is evaluated. These sections detail the processing conditions, positive and negative effects, as well as possible applications of the extracted pigments. This review presents relevant information that may be useful to expand and explore new applications of ultrasound technology as well as promote the revaluation of by-products to obtain pigments that can be used in food, pharmaceutical or cosmetic industries.